2021
DOI: 10.1134/s0036024421100204
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Numbers of Bivalent Ions in Organic Solvents

Abstract: Molecular dynamic models are created for properties of bivalent ions in organic solvents. It is shown that molecules of the considered solvents bound to ions via oxygen atoms. A theoretical model is developed that describes the ion coordination number. The coordination number in this model is determined by the ratio between the sizes of the ion and the atom organic molecule bound to it. It is shown that the coordination number depends weakly on the solvent and strongly on the type of ion. A value of 0.13 nm is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The chloride ions test in all complexes was done with the AgNO 3 solution, and a negative result was obtained [18]. The molar conductance values of the complexes in DMSO solvent indicated that [ML 1 L 2 ] complexes are non-electrolytes, while complex 2 is a 1:1 electrolyte [19][20]. These results support the proposed formula of the complexes (Fig.…”
Section: ■ Results and Discussionsupporting
confidence: 55%
“…The chloride ions test in all complexes was done with the AgNO 3 solution, and a negative result was obtained [18]. The molar conductance values of the complexes in DMSO solvent indicated that [ML 1 L 2 ] complexes are non-electrolytes, while complex 2 is a 1:1 electrolyte [19][20]. These results support the proposed formula of the complexes (Fig.…”
Section: ■ Results and Discussionsupporting
confidence: 55%
“…According to different sources, the ionic radii for Ca 2+ and Mg 2+ ions have the value r(Ca 2+ ) = 0.99-1.14 Å, while for Mg 2+ , it is smaller: r(Mg 2+ ) = 0.69-0.89 Å [39,[70][71][72]. This difference is responsible for the observed shrinkage of the cell.…”
Section: Unit Cell Parametersmentioning
confidence: 99%
“…When all positions of substitutions of Mg/Ca1 ions around the axis of the OH channel become occupied (the case of 16 Mg/Ca1, x = 2), the symmetry is practically restored (last column in Table S2.2). The Mg ions in Ca1 positions at a Mg concentration x = 2 already strongly interact with the oxygen ions of the surrounding PO 4 groups (Figure 5b), forming saturated ionic bonds up to an amount corresponding to their coordination number, which is equal to 6 [72].…”
Section: Distances From Oh Channel To Atoms In the Ca1 Positionsmentioning
confidence: 99%
See 2 more Smart Citations